Point of Care Ultrasound Identification of Multiple Rib Fractures in a Pediatric Patient with Osteogenesis Imperfecta Type 3 - Samuel Enci Quek; Vigil James; Leodivica Castillo; Ronald Ming Ren Tan; Gene Yong-Kwang Ong (MDPI AG, 2022)
Patients with osteogenesis imperfecta (OI) are at an increased risk of pathological rib fractures even if there is no history of trauma. Early and accurate identification of such fractures are crucial for appropriate management. We present a case of a child with OI type 3 with multiple rib fractures who presented with transient cyanosis and increased work of breathing without a history of significant trauma. The patient's chest radiographs were reported to have a single, new right posterior fourth rib fracture and an old, healing anterior fourth rib fracture. A point-of-care ultrasound performed by the attending pediatric emergency physician revealed additional findings of refracture over the old right anterior fourth rib fracture site and a new left posterior third rib fracture. These findings of multiple and bilateral rib fractures better account for the patient's initial presentation. This case highlights the added advantages of ultrasound over conventional chest radiographs in the evaluation and diagnosis of a tachypnoeic pediatric patient with underlying metabolic bone disease and a complex skeletal structure with multiple pathological rib fractures but no chest tenderness.